MICROBIAL EXOPOLYSACCHARIDE-BASED HYDROGELS FOR BURN WOUND HEALING (Experimental biology, 2025)
This review examines innovative approaches to the treatment of burn injuries through the use of microbial polysaccharides, highlighting their unique properties such as wound infection prevention, moisture retention, and acceleration of tissue regeneration. The development of novel, natural-based pharmaceutical formulations in a patient-friendly dosage form is necessitated by the complexity and high cost of burn treatment, which, in severe cases, may result in fatal outcomes.An analysis of the pharmaceutical market in Kazakhstan reveals a shortage of multifunctional anti-burn drugs and a limited utilization of natural-origin active compounds (17.6% natural components, 82.4% synthetic components). Hydrogels, as a dosage form, offer notable advantages due to their unique physicochemical properties. They maintain a moist wound environment, regulate the release of active substances, ensure direct contact with the injured area, and act as a protective barrier against infection.Microbial polysaccharides, owing to their ability to form three-dimensional network structures, are particularly promising as a foundational material for hydrogels. A detailed examination of the composition and properties of hydrogels based on microbial polysaccharides underscores the potential of biopolymeric compounds in the development of accessible and effective wound-healing formulations. ...
Keywords: burn wound healing, microbial exopolysaccharide, hydrogels, pullulan, dextran, alginate, hyaluronic acid